Ionomic and metabolic responses to neutral salt or alkaline salt stresses in maize (Zea mays L.) seedlings. Issue 1 (December 2017) - Guo, Rui; Shi, LianXuan; Yan, Changrong; Zhong, Xiuli; Gu, FengXue; Liu, Qi; Xia, Xu; Li, Haoru
Abstract Background Soil salinity and alkalinity present a serious threat to global agriculture. However, most of the studies have focused on neutral salt stress, and the information on the metabolic responses of plants to alkaline salt stress is limited. This investigation aimed at determining the influence of neutral salt and alkaline salt stresses on the content of metal elements and metabolites in maize plant tissues, by using mixtures of various proportions of NaCl, NaHCO3, Na2 SO4, and Na2 CO3 . Results We found that alkaline salt stress suppressed more pronouncedly the photosynthesis and growth of maize plants than salinity stress. Under alkaline salt stress conditions, metal ions formed massive precipitates, which ultimately reduced plant nutrient availability. On the other hand, high neutral salt stress induced metabolic changes in the direction of gluconeogenesis leading to the enhanced formation of sugars as a reaction contributing to the mitigation of osmotic stress. Thus, the active synthesis of sugars in shoots was essential to the development of salt tolerance. However, the alkaline salt stress conditions characterized by elevated pH values suppressed substantially the levels of photosynthesis, N metabolism, glycolysis, and the production of sugars and amino acids. Conclusions These results indicate the presence of different defensive mechanisms responsible for the plant responses to neutral salt and alkaline salt stresses. In addition, the increased concentration of organic acids and enhanced metabolic energy might be potential major factors that can contribute to the maintenance intracellular ion balance in maize plants and counteract the negative effects of high pH under alkaline salt stress.